Efficacy of Riparian Buffers in Phosphorus Removal: A Meta-Analysis - Tsai, Yushiou; Zabronsky, Hope M.; Zia, Asim; Beckage, Brian (Frontiers in Water, 2022)
Efficacious use of riparian buffers is one mitigation strategy that can protect water quality in the face of climate change and agricultural intensification. We investigate the efficacy of riparian buffers (RBs) in reducing phosphorus (P) and identify effective RB designs using two quantitative meta-analytic approaches—traditional random-effects and Bayesian mixed-effects regression—to synthesize results from 36 peer-reviewed articles. We find that overall P removal efficacy of RBs is 54.5% with a 95% confidence interval (46.1, 61.6), as indicated by our traditional meta-analysis, and 51.3% on average with a 95% confidence level (19.6, 71.2), as estimated by our Bayesian meta-analysis. The effectiveness of RBs was reduced by soil that was either bare, water-saturated, or covered by snowmelt. The interactive effect of width and slope on P removal in RBs varied considerably across different soils, leading to a larger variation in P removal efficacy, as compared to other studies. Our results show that width is the predominant determinant for P retention efficiency in clay soil RBs, whereas in sandy soil RBs slope is the leading factor. Our findings can provide policy makers and managers with RB design criteria to maximize P retention.